2017
DOI: 10.1002/sce.21271
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Practices of Engineering for Education

Abstract: Engineering offers new educational opportunities for students, yet also poses challenges about how to conceptualize the disciplinary core ideas, crosscutting concepts, and science and engineering practices of the disciplinary fields of engineering. In this paper, we draw from empirical studies of engineering in professional and school settings to propose a set of epistemic practices of engineering that can inform curriculum development, teacher education, and research in science and engineering education. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
270
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(283 citation statements)
references
References 71 publications
5
270
0
8
Order By: Relevance
“…Through the layering of pancakes, Christopher took an ill‐structured problem and optimized it given the resources and tools he had available, and sought—in collaboration with his community—to make available. While others (e.g., Cunningham & Kelly, , Dym, Agogino, Eris, Frey, & Leifer, ) have indicated that this process is argumentative, as engineers engage in dialogue with each other about the affordances of different designs, Christopher kept in dialog with his community, leveraging upon their wisdom to inform his design decision. We see this as different from engaging with clients in ways that help to better set parameters and constraints (Hynes & Swenson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Through the layering of pancakes, Christopher took an ill‐structured problem and optimized it given the resources and tools he had available, and sought—in collaboration with his community—to make available. While others (e.g., Cunningham & Kelly, , Dym, Agogino, Eris, Frey, & Leifer, ) have indicated that this process is argumentative, as engineers engage in dialogue with each other about the affordances of different designs, Christopher kept in dialog with his community, leveraging upon their wisdom to inform his design decision. We see this as different from engaging with clients in ways that help to better set parameters and constraints (Hynes & Swenson, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that it is important to develop an understanding of the engineering design process as Cunningham and Kelly (2017) stated that this could help to teach science and that "engineering offers ways of knowing that it can be educative beyond just servicing science learning" (p.498). Hertel et al (2017) have done research to find out the effect of notebooks on students" learning through engineering design activities.…”
Section: Related Research In the Literaturementioning
confidence: 99%
“…As the end product in engineering design is primarily a technological product, this connection may not be as strong between the knowledge of engineering and reading and writing about engineering, the fundamental sense of what could be deemed engineering literacy. However, when considering the epistemic practices of engineering 2 , it is clear that the nature of engineering necessitates a certain facility with disciplinary writing, particularly in the practice of recording data from testing and utilizing it in design decisions.…”
Section: Notebooking In Elementary Engineering Educationmentioning
confidence: 99%
“…Realworld engineering design challenges are open-ended-multiple solutions to the problem exist 2 . A challenge engineering introduces into classrooms is how classes can be structured so that they afford students the opportunity to think creatively and generate new solutions as they engage in the types of conversations and deliberations that occur in engineering teams.…”
Section: Introductionmentioning
confidence: 99%